Evaluation of the agricultural potential of the serpentinite rock as a soil remineralizer - VIANA,JOÃO H.M. (2021)
Abstract Magnesium is one of the essential elements for the plant growth. However, when the supply of magnesium is required exclusively, few economically feasible options are available. Serpentinite represents an alternative source of magnesium, although little is known about its potential and efficiency under tropical soil conditions. This work aimed to evaluate the use of serpentinite as a soil remineralizer, as well as magnesium fertilizer. The study was conducted in a greenhouse, using a completely randomized design, with seven treatments and four replications, as follows: three levels of serpentinite, mix of serpentinite and phonolite, and the controls with dolomitic limestone and without fertilization. Two plant species (Zea mays L. corn hybrid BRS – 1055 and Phaseolus vulgaris L. common bean variety BRS – Estilo) and two contrasting soils (clayey and sandy texture), were used in pots. Results showed that serpentinite’s free silica and toxic element contents fitted the legal requirements. No statistically significant difference was observed for the plant dry matter weight production in the serpentinite and dolomitic limestone control, as well as in the pure serpentinite and the mix with phonolite treatments. The serpentinite was able to supply and to fullfil magnesium requirements for growth and development of corn and bean plants.